Potential Economic Benefits of Limited Clinical and Radiographic Follow-up After Plate Fixation of Midshaft Clavicle Fractures. Issue 11 (1st June 2019) - Sanchez Morales, Daniela; Borade, Amrut; Serrano-Riera, Rafael; Maniar, Hemil H.; Sanders, Roy W.; Horwitz, Daniel Scott
Abstract : Introduction: The role of routine clinical and radiographic follow-up after clavicle fractures are healed was evaluated. Methods: A retrospective study performed in two level-1 trauma centers included 246 adults with healed clavicle fractures treated surgically between 2000 and 2013 and at least 24-month follow-up. Based on radiographs, changes in fracture alignment or implant position from union to final follow-up were documented. The average reimbursement for a follow-up clinical visit and a clavicle radiograph was estimated. Results: Mean time to union and mean time of follow-up were of 4.8 and 31.4 months, respectively. No changes in implant position or fracture alignment occurred after the fracture had healed. The amount reimbursed to our institution for two clinical visits and two clavicle radiographs was approximately 300 to 540. Conclusion: Once clavicle fractures are healed, further radiographic imaging does not provide any notable information. Limiting routine follow-up is safe and could be cost-effective for the healthcare system. Level of Evidence: Level-III retrospective cohort study